Effect of Pjbl Model and Preliminary Knowledge on Critical Thinking Skills of Grade Iv Students of Kartika Elementary School 1-11 Kota Padang - Dian Puspita Sari; Abna Hidayati; Yanti Fitria; Mudjiran Mudjiran (International Journal of Educational Dynamics, 2019)
This quasi-experimental study was to find out: (1) the influence of critical thinking skills of students given the Project Based Learning (PjBL) model with students who were given conventional learning; (2) the influence of critical knowledge with high initial knowledge using the Project Based Learning (PjBL) model compared to those using conventional learning; (3) the influence of critical thinking skills with low initial knowledge using the Project Based Learning (PjBL) model compared to those using conventional learning; (4) interaction between learning strategies with students' initial knowledge of critical thinking skills. This research is a quasi-experimental type with a research design using factorial 2x2. The population is all SD Kartika 1-11 students and the sample is 50 IVA and IVB students. The sampling technique is simple random sampling. Research data was obtained from tests of initial knowledge and critical thinking skills. The results of the study indicate that: (1) students' critical thinking skills given the Project Based Learning (PjBL) model higher tcount = 1.910> t table = 1.708; (2) Critical thinking skills with high initial knowledge using the Project Based Learning (PjBL) and conventional models have no significant differences thitung = 1.87 <ttable = 2.56; (3) Critical thinking skills with low initial knowledge use the Project Based Learning (PjBL) model higher t count = 3.71> t table = 2.56; (4) there is no interaction between learning models with students' initial knowledge of critical thinking skills. Keywords: PJBL, Preliminary Knowledge, Critical Thinking Skills.